Genetically predicted metabolite mediates the causal relationship between immune cells and autoimmune diseases - Jinpeng Wei; Jian Li; Tianyang Li; Tao Xu; Yingchi Zhang; Shuhan Yang; Hua Wu; Haihu Hao (Arthritis Research & Therapy)
Abstract Background This study investigates the causal role of metabolites mediating immune cells in rheumatoid arthritis (RA) and ankylosing spondylitis (AS) through a Mendelian randomization (MR) study. Methods The two-sample and two-step MR methods were used for the current analysis: (1) causal effects of immune cells on RA and AS; (2) mediation effects of metabolites. Inverse variance weighted (IVW) is the main method to analyze causality, and MR results are verified by several sensitive analyses. Results This study first identified the immune cells and metabolites that are causally associated with RA and AS, respectively. Subsequent mediation analyses revealed that of the 61 metabolic factors that were causally associated with RA, 6 were identified as mediators of the relationship between immune cells and RA, including 4-cholesten-3-one levels (mediation ratio: 8.91%), N-lactoyl isoleucine levels (13%), 3- phosphoglycerate to glycerate ratio (12.9%, 2.31%, respectively), Gamma-glutamyl histidine levels (9.54%), and Citrulline to phosphate ratio (15.6%). Among the 52 metabolic factors that were causally associated with AS, 2 were identified as mediators of the relationship between immune cells and AS, including salicylate levels (10.4%) and Glucose to N-palmitoyl-sphingosine (d18:1 to 16:0) ratio (8.72%). These results performed well in sensitivity analysis. Conclusions Genetic predictions show causal relationships between immune cells and autoimmune diseases, and that these causal relationships can be mediated by certain metabolites as mediators.